High-impact modifier as well as preparation method and application thereof
Preparation of high-impact modifiers through emulsion polymerization and graft polymerization processes solves the problems of cumbersome operation and limited improvement of toughening performance in the prior art, and achieves significant toughening effect and other properties of PVC resins .
Patent Information
- Application Number
- CN202411802079.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-02-11
AI Technical Summary
The prior art is complicated to operate in improving the impact strength of AAS copolymers and has limited improvement in toughening performance. Introducing too many inorganic salts during the polymerization process can easily cause the emulsion system to be instable and affect product yield.
Seed latex is prepared by emulsion polymerization, followed by diameter expansion reaction, followed by graft polymerization with styrene and acrylonitrile, and finally obtained a high impact modifier after coagulation, centrifugation and drying. This method simplifies the process flow and replaces butyl acrylate by partial hexyl acrylate, reducing the glass transition temperature of the rubber phase and improving the impact modification effect.
This method greatly improves the toughening and modification effect of AAS polymer on PVC resin, improves impact resistance by more than 20%, while maintaining other properties unchanged, and has a simple process and good operability.
Smart Images

Figure BDA0005178285460000041 
Figure BDA0005178285460000051 
Figure BDA0005178285460000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastic modification, and in particular to a weather-resistant and high-impact modifier and a preparation method and application thereof. Background Art
[0002] Butyl acrylate-styrene-acrylonitrile (AAS) copolymer is a new type of polymer with a typical soft-core and hard-shell structure synthesized under the concept of particle design. It is prepared by grafting acrylonitrile and styrene on acrylic rubber. Its structure is that the rubber phase is dispersed in the continuous phase of SAN to form an "island" structure, rather than just a copolymer of three components. In addition to its remarkable weather resistance, it also has the following characteristics: (1) Impact resistance: It maintains a high impact strength over a wide temperature range; (2) Mechanical strength: It has good tensile strength, flexural strength and rigidity, and these properties are balanced; (3) Heat resistance: It does not lose strength or deform at high temperatures, and has excellent thermal stability; (4) High electrical insulation; (5) Chemical resistance: It can resist alkali, animal oil, and vegetable oil; (6) It has very good colorability and can be dyed into various bright colors; (7) It has excellent processing performance and can be processed by conventional molding machinery.
[0003] Continuously improving the impact strength of the prepared AAS copolymer has always been a hot topic in this field. The Chinese patent with application number 201010245995.X emphasizes the method of adding potassium persulfate and SDS in batches, adding a small part initially, and continuing to drip most of the KPS aqueous solution and SDS aqueous solution respectively after the monomers are fully added. Compared with the one-time addition of KPS and SDS, its impact strength can be significantly improved. The disadvantage of this patent is that the operation process is relatively cumbersome, and the improvement of toughening performance is limited. The Chinese patent with application number 201410490467.9 adopts seed emulsion polymerization and moderate cross-linking of the expansion layer, shell pre-swelling, pre-emulsification and dripping process, which improves the conversion rate and grafting rate, and also achieves the toughening effect. It introduces too many inorganic salts in the polymerization process, which improves the expansion effect while also easily causing the instability of the emulsion system, and may cause too much gel, affecting the final product yield. US 3898301 adopts a method of blending large-particle-size and small-particle-size latexes, wherein small-particle-size PBA latex and large-particle-size PBA latex are mixed in a certain ratio to obtain a rubber latex with a wide particle size distribution, and the small particle size produces silver streaks, and the large particle size produces shear bands to improve the impact performance. The preparation thereof requires the simultaneous production of two latexes with different particle sizes, and the process is relatively long, the toughening effect is limited, and it is not economical. There are also reports of first preparing a cross-linked styrene core PBA rubber latex and then grafting it to prepare an AAS polymer, but the Tg of styrene is significantly higher than that of butyl acrylate, so the effect of improving toughness cannot be achieved. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a high impact modifier and its preparation method and application. The modifier prepared by the present invention can greatly improve the toughening and modification effect of AAS polymer on PVC resin while keeping other properties unchanged.
[0005] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0006] In a first aspect, the present invention provides a method for preparing a high impact modifier, comprising the following steps:
[0007] (1) preparing a seed latex by emulsion polymerization using butyl acrylate and hexyl acrylate as mixed monomers, wherein the mass ratio of butyl acrylate to hexyl acrylate is 80-99:1-20;
[0008] (2) continuing to react the seed latex obtained in step (1) with butyl acrylate and hexyl acrylate to obtain a rubber latex with an expanded diameter; wherein the mass ratio of butyl acrylate to hexyl acrylate is 80-99:1-20;
[0009] (3) mixing the expanded rubber latex obtained in step (2) with styrene and acrylonitrile to carry out graft polymerization to obtain a copolymer latex;
[0010] (4) The copolymer latex obtained in step (3) is coagulated, centrifuged and dried in sequence to obtain the high impact modifier.
[0011] It should be noted that hexyl acrylate is n-hexyl acrylate, with the structural formula:
[0012] The following is a detailed description:
[0013] Step (1):
[0014] In some embodiments, the mass content of butyl acrylate in the mixed monomer is 80%-99%, and the mass content of hexyl acrylate is 1%-20%;
[0015] In some embodiments, the total amount of the acrylate monomer is 100 parts by weight, and step (1) comprises the following steps:
[0016] (1.1) Add 180-240 parts by weight of water and 0.75-1 parts by weight of emulsifier into a polymerization kettle under nitrogen protection and stir evenly;
[0017] (1.2) heating, and then adding 80-99 parts by weight of butyl acrylate, 1-20 parts by weight of hexyl acrylate and 0.1-5.0 parts by weight of a cross-linking agent;
[0018] (1.3) Then, a solution of 0.1-0.5 parts by weight of an initiator and 10-30 parts by weight of water is added in batches, and the reaction is continued. When the conversion rate reaches more than 95%, the reaction is stopped and the material is discharged.
[0019] The emulsifier can be sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium oleate, etc.
[0020] The crosslinking agent may be ethylene glycol dimethacrylate, divinylbenzene, diallyl phthalate, or the like.
[0021] The initiator can be potassium persulfate, ammonium persulfate, hydrogen peroxide, etc.
[0022] Preferably, in step (1.2), the temperature is raised to 55-65°C;
[0023] Preferably, the reaction time in step (1.3) is 3-5 h.
[0024] Step (2):
[0025] In some embodiments, the total amount of the acrylic acid ester monomer for diameter expansion is 100 parts by weight, and step (2) comprises the following steps:
[0026] (2.1) Add 5-20 parts by weight of seed latex (based on dry latex) and 180-240 parts by weight of water into a polymerization kettle under nitrogen protection and stir evenly;
[0027] (2.2) Then add the following components in batches: 80-99 parts by weight of butyl acrylate, 1-20 parts by weight of hexyl acrylate, 0.1-5.0 parts by weight of crosslinking agent, 0.1-0.5 parts by weight of emulsifier, and 0.1-0.5 parts by weight of initiator, raise the temperature to continue the reaction, and discharge the material.
[0028] Preferably, in step (2.2), the temperature is raised to 55-65° C. and the reaction is carried out for 3-5 hours.
[0029] Step (3):
[0030] In some embodiments, the graft polymerization in step (3) is a one-step graft polymerization or a two-step graft polymerization;
[0031] The one-step graft polymerization is to mix the expanded rubber latex with all styrene and acrylonitrile at one time for graft polymerization;
[0032] The two-step graft polymerization comprises firstly mixing the expanded rubber latex with half of the styrene and acrylonitrile to carry out a first graft reaction, and then mixing the obtained graft product with the remaining monomers to carry out a second graft reaction.
[0033] In some embodiments, the total amount of the grafting monomer is 100 parts by weight, and step (3) comprises the following steps:
[0034] (3.1) Add 100-400 parts by weight of the expanded rubber latex (calculated as dry rubber) and 10-20 parts by weight of water into a polymerization kettle and stir evenly;
[0035] (3.2) Raise the temperature, then add the following components in batches: 25-75 parts by weight of styrene, 25-75 parts by weight of acrylonitrile, 0.1-1.0 parts by weight of an organic peroxide initiator, and then add in batches a solution of 0.1-0.5 parts by weight of a reducing agent, 0.01-0.03 parts by weight of a complexing agent, 0.001-0.01 parts by weight of a reducing agent and 90-120 parts by weight of water, continue the reaction, and discharge the material.
[0036] The organic peroxide initiator can be diisopropylbenzene hydroperoxide, isopropylbenzene hydroperoxide, tert-butyl hydroperoxide, etc.
[0037] The reducing agent can be ferrous sulfate, ferrous chloride, etc.;
[0038] The auxiliary reducing agent may be Rongbai, glucose, etc.;
[0039] The complexing agent can be ethylenediammonium tetraacetic acid disodium salt, ethylenediammonium tetraacetic acid tetrasodium salt, ethylenediammonium tetraacetic acid sodium ferrate salt, etc.
[0040] Preferably, in step (3.2), the temperature is raised to 55-65° C. and the reaction is carried out for 1-3 hours.
[0041] Step (4):
[0042] The coagulant used for the coagulation can be calcium chloride, magnesium chloride, aluminum sulfate, etc.
[0043] The present invention has no particular limitation on the specific parameters of the coagulation, centrifugation and drying, and methods well known to those skilled in the art may be used.
[0044] In a second aspect, the present invention provides a high impact modifier prepared by the above preparation method.
[0045] In a third aspect, the present invention provides an application of the above-mentioned high impact modifier as a toughening agent in the field of general plastics.
[0046] The high impact-resistant modifier obtained by the invention can greatly improve the toughening effect on PVC resin without affecting other properties.
[0047] In the process of polymer modification, glass transition temperature is one of the key factors affecting toughening performance. According to the difference in glass transition temperature, monomers can be divided into three categories: the first is hard monomers with a temperature of >40°C, the second is soft elastic monomers with a temperature of <-10°C, and the third is monomers with moderate hardness and softness between the above two. Under the same conditions, the lower the glass transition temperature of the homopolymer, the better its impact resistance. The glass transition temperatures of various commonly used polymer materials are shown in Table 1:
[0048] Table 1 Glass transition temperature of commonly used polymer homopolymers
[0049]
[0050]
[0051] It can be seen from the data in Table 1 that the glass transition temperature of butyl acrylate used to synthesize AAS resin is -54°C. To improve the impact resistance, hexyl acrylate with a lower glass transition temperature can be used. However, from the perspective of using it as a PVC modifier, considering the stability of its polymerization system and its economic deficiencies, its usage should be limited.
[0052] Based on this, the present invention, based on the existing AAS polymer synthesis technology, carried out an experiment of using part of hexyl acrylate to replace butyl acrylate in rubber latex, so as to further reduce the glass transition temperature of the rubber phase and achieve the purpose of improving the impact modification effect.
[0053] The present invention first synthesizes butyl acrylate and hexyl acrylate seed latex, then expands butyl acrylate and hexyl acrylate to obtain rubber latex with suitable particle size, then adopts styrene and acrylonitrile for graft polymerization to obtain copolymer latex, and finally obtains AAS polymer (i.e. high impact modifier) through condensation, centrifugation and drying. Afterwards, the processing and test performance comparison of AAS resin modified PVC obtained by the above different processes are completed according to conventional mixing, melting, tableting, sample preparation and testing processes. Compared with the original conventional modification, the notched impact resistance of PVC resin modified by the polymer can be improved by more than 20%, and other indicators such as the apparent density of the polymer and the tensile properties of the resin are not affected.
[0054] Compared with the prior art, the present invention can greatly improve the toughening and modification effect of AAS polymer on PVC resin, while keeping other properties unchanged. In addition, the present invention has a simple synthesis process and good operability.
[0055] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. DETAILED DESCRIPTION
[0056] The present invention is further described below in conjunction with examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed for the present invention.
[0057] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.
[0058] Example 1
[0059] (1) Synthesis of seed latex
[0060] Under nitrogen protection, the following components were added sequentially into a stirred normal pressure polymerization reactor:
[0061] 200 parts of softened water
[0062] 0.833 parts of sodium lauryl sulfate
[0063] After stirring evenly, heat to 58°C and then add the following mixture:
[0064] Butyl acrylate 90 parts
[0065] Hexyl acrylate 10 parts
[0066] Diallyl phthalate 0.75 parts
[0067] After 5 minutes, potassium persulfate aqueous solution was added once every 30 minutes, and the total amount was a mixture of 0.25 parts of potassium persulfate and 20 parts of softened water. The reaction was continued for 4 hours until the conversion rate reached 98%, and then the material was discharged to obtain seed rubber latex, which was measured to have a solid content of 31% and a particle size of 98 nm.
[0068] (2) Synthesis of expanded latex
[0069] Under nitrogen protection, the following components were added sequentially into a stirred normal pressure polymerization reactor:
[0070] Seed latex (S = 31%, based on dry rubber) 10 parts
[0071] 204 parts of softened water
[0072] Then, add the following mixture in two equal portions at 2 hr intervals:
[0073]
[0074] After the addition was completed, the temperature was raised to 58°C and the reaction was continued for 4 hours, the conversion rate was 98%, and then the material was discharged to obtain the expanded latex. The solid content of the latex was measured to be 35%, and the particle size was 240nm.
[0075] (3) Synthesis of copolymer latex
[0076] Add the following components in sequence into a stirred normal pressure polymerization reactor:
[0077] Expanded latex (S = 35%, based on dry rubber) 185 parts (latex amount is 527 parts)
[0078] 15.3 parts of softened water
[0079] Start stirring, raise the temperature to 55°C, and add the following components in two equal amounts:
[0080] Styrene 50 parts
[0081] Acrylonitrile 50 parts
[0082] After 5 minutes, add 0.50 parts of diisopropylbenzene hydroperoxide twice to the aqueous solution containing the following components:
[0083]
[0084]
[0085] After the polymerization was continued for 2 hours, a copolymer latex was obtained, and its solid content was measured to be 38% and its particle size was 260 nm.
[0086] The obtained copolymer latex was cooled to room temperature, then coagulated with 2.5% calcium chloride, centrifuged and dried to obtain AAS resin, i.e., high impact modifier. The apparent density data is shown in Table 2.
[0087] The impact and tensile properties of the obtained AAS polymer were tested by fully mixing according to the following ratio:
[0088]
[0089] The obtained blend was mixed and plasticized on a double-roll mixer at a mixing temperature of 175±5°C. After mixing for 5 minutes, a sheet was drawn and then pressed into a 4 mm thick sheet on a hot press at a pressing temperature of 180±2°C. After pressing for 3 minutes, the sheet was cooled and the test specimens were prepared according to the national standard method. The MFR, tensile strength and notched impact resistance tests were carried out. The performance test results are shown in Table 2.
[0090] Example 2
[0091] In the above Example 1, the ratio of butyl acrylate to hexyl acrylate in the rubber latex synthesis was adjusted to 95:5, and the rest was the same as Example 1. The performance test results are shown in Table 2.
[0092] Example 3
[0093] In the above Example 1, the ratio of butyl acrylate to hexyl acrylate in the synthesis of rubber latex was adjusted to 80:20, and the rest was the same as Example 1. The performance test results are shown in Table 2.
[0094] Example 4
[0095] In the above Example 1, the ratio of butyl acrylate to hexyl acrylate in the synthesis of rubber latex was adjusted to 85:15, and the rest was the same as Example 1. The performance test results are shown in Table 2.
[0096] Example 5
[0097] In the above Example 1, the ratio of butyl acrylate to hexyl acrylate in the rubber latex synthesis was adjusted to 98:2, and the rest was the same as Example 1. The performance test results are shown in Table 2.
[0098] Example 6
[0099] In the above Example 1, the styrene and acrylonitrile monomers in the copolymer latex synthesis were added at one time, and the rest was the same as Example 1. The performance test results are shown in Table 2.
[0100] Comparative Example 1
[0101] In the above Example 1, butyl acrylate was used to replace hexyl acrylate, and the rest was exactly the same as in Example 1. The performance test results are shown in Table 2.
[0102] Comparative Example 2
[0103] In the above Example 1, the ratio of butyl acrylate to hexyl acrylate in the rubber latex synthesis process was adjusted to 70:30, and the rest was exactly the same as in Example 1. During the test, significantly more jelly appeared, and the performance test results are shown in Table 2.
[0104] Table 2 Effect of comprehensive physical properties of AAS resin and its mixture
[0105]
[0106] It can be seen from the table that compared with the original resin, the impact resistance of the AAS resin prepared by the present invention is improved by more than 20% under the premise that other properties remain basically unchanged.
[0107] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents, without departing from the spirit and essence of the claims of the present invention; and these modifications or replacements are still within the scope defined by the claims of the present invention.
Claims
1. A method for preparing a high impact modifier, characterized in that: The following steps are involved: (1) preparing a seed latex by emulsion polymerization using butyl acrylate and hexyl acrylate as mixed monomers; wherein the mass ratio of butyl acrylate to hexyl acrylate in step (1) is 80-99:1-20; (2) continuing to react the seed latex obtained in step (1) with butyl acrylate and hexyl acrylate to obtain a rubber latex with an expanded diameter; wherein the mass ratio of butyl acrylate to hexyl acrylate in step (2) is 80-99:1-20; (3) mixing the expanded rubber latex obtained in step (2) with styrene and acrylonitrile to carry out graft polymerization to obtain a copolymer latex; (4) The copolymer latex obtained in step (3) is coagulated, centrifuged and dried in sequence to obtain the high impact modifier.
2. The preparation method according to claim 1, characterized in that: The total amount of the acrylate monomer is 100 parts by weight, and step (1) comprises the following steps: (1.1) Add 180-240 parts by weight of water and 0.75-1 parts by weight of emulsifier into a polymerization kettle under nitrogen protection and stir evenly; (1.2) heating, and then adding 80-99 parts by weight of butyl acrylate, 1-20 parts by weight of hexyl acrylate and 0.1-5.0 parts by weight of a cross-linking agent; (1.3) Then, a solution of 0.1-0.5 parts by weight of an initiator and 10-30 parts by weight of water is added in batches, and the reaction is continued. When the conversion rate reaches more than 95%, the reaction is stopped and the material is discharged.
3. The preparation method according to claim 2, characterized in that: In step (1.2), the temperature is raised to 55-65°C; The reaction in step (1.3) is carried out for 3-5 hours.
4. The preparation method according to claim 1, characterized in that: The total amount of the acrylic acid ester monomer for diameter expansion is 100 parts by weight, and step (2) comprises the following steps: (2.1) Add 5-20 parts by weight of seed latex and 180-240 parts by weight of water into a polymerization kettle under nitrogen protection and stir evenly; (2.2) Then add the following components in batches: 80-99 parts by weight of butyl acrylate, 1-20 parts by weight of hexyl acrylate, 0.1-5.0 parts by weight of crosslinking agent, 0.1-0.5 parts by weight of emulsifier, and 0.1-0.5 parts by weight of initiator, raise the temperature to continue the reaction, and discharge the material.
5. The preparation method according to claim 4, characterized in that: In step (2.2), the temperature is raised to 55-65°C and the reaction is carried out for 3-5 hours.
6. The preparation method according to any one of claims 2 to 5, characterized in that: The emulsifier is one or more selected from sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and sodium oleate; The cross-linking agent is one or more selected from ethylene glycol dimethacrylate, divinylbenzene, and diallyl phthalate; The initiator is one or more selected from potassium persulfate, ammonium persulfate and hydrogen peroxide.
7. The preparation method according to claim 1, characterized in that: The total amount of the grafted monomer is 100 parts by weight, and step (3) comprises the following steps: (3.1) Add 100-400 parts by weight of the expanded rubber latex and 10-20 parts by weight of water into a polymerization kettle and stir evenly; (3.2) Raise the temperature, then add the following components in batches: 25-75 parts by weight of styrene, 25-75 parts by weight of acrylonitrile, 0.1-1.0 parts by weight of an organic peroxide initiator, and then add in batches a solution of 0.1-0.5 parts by weight of a reducing agent, 0.01-0.03 parts by weight of a complexing agent, 0.001-0.01 parts by weight of a reducing agent and 90-120 parts by weight of water, continue the reaction, and discharge the material.
8. The preparation method according to claim 7, characterized in that: The organic peroxide initiator in step (3.2) is one or more selected from diisopropylbenzene hydroperoxide, isopropylbenzene hydroperoxide, and tert-butyl hydroperoxide; The reducing agent in step (3.2) is one or more selected from ferrous sulfate and ferrous chloride; The auxiliary reducing agent in step (3.2) is one or more selected from Rongbai and glucose; The complexing agent in step (3.2) is one or more selected from ethylenediammonium tetraacetate disodium salt, ethylenediammonium tetraacetate tetrasodium salt, and ethylenediammonium tetraacetate sodium ferrate salt; In step (3.2), the temperature is raised to 55-65°C and the reaction is carried out for 1-3 hours.
9. A high impact modifier, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the high impact modifier according to claim 9 as a toughening agent in the field of general plastics.
Citation Information
Patent Citations
Preparation method of weather resistant and impact resistant modified resin
CN102344635A
Preparation method of ASA (acrylonitrile styrene acrylate) powder
CN104231185A
Blends of thermoplastic polymers with graft copolymers of maleic acid derivatives
US3898301A